OPTIMIZING WATER PROVISIONING SERVICES OF FOREST PLANTATIONS IN WATER SCARCE AREAS: A COST-BENEFIT ANALYSIS OF REFORESTATION APPROACHES IN MAASIN WATERSHED FOREST RESERVE, ILOILO - YUJI DECENA ENRIQUEZ (2019)
Master's